Analysis of Depression Levels in Type 2 Diabetes Mellitus Patients at 'Aisyiyah General Hospital Ponorogo - Gandes Widya Hendrawati; Nurul Uswiyah Huda; Agung Eko Hartanto; Dwi Setiani; Agus Wiwit Suwanto; Lina Septina Dewi (KHD Production, 2024)
Diabetes mellitus type 2 is a common health problem in Indonesia. Depressive symptoms are common among adults with diabetes. Clinically significant depression is present in one of every four people with type 2 diabetes mellitus. A diagnosis of type 2 diabetes mellitus increases the risk of incident depression and can contribute to a more severe course of depression. The aim of the study was to estimate the prevalence of depression in the population diagnosed with diabetes type 2. Respondens were patient with type 2 diabetes mellitus in Kardinah Hospital. This research is quantitative descriptive. The sampling technique using accident sampling with 60 individuals with type 2 diabetes mellitus. The data was taken by instrument using PH9. Data was analyzed by univariate test. The result of the analysis 82,3% no symptom of depression and 17,7% have a depression. Depression at all levels in DM sufferers cannot be ignored, intervention must be obtained. Because depression makes health problems worse.